Unfractionated Heparin for the Treatment of Venous Thromboembolism: Best Practices and Areas of Uncertainty - Cuker, Adam (Seminars in Thrombosis and Hemostasis, 2012)
Nearly 100 years after its discovery, unfractionated heparin (UFH) remains a widely used anticoagulant for the treatment of venous thromboembolism (VTE) and several other thrombotic and prothrombotic conditions. Decades of experience and investigation have contributed to our knowledge of this agent, but crucial questions regarding its optimal use in clinical practice remain unanswered. This review will critically examine the evidence for dosing and laboratory monitoring of UFH in the management of VTE, and highlight areas of uncertainty and future research.
Keywords: heparin; unfractionated heparin; venous thromboembolism; dosing; laboratory monitoring